Development of a time gated, compressive detection Raman instrument for effective fluorescence rejection and multilayer analysis - Corden, Christopher James (2021)
In this thesis we have developed and implemented a Raman instrument of a novel design that uses a combination of state-of-the-art technologies to provide a temporal dimension in the measured spectrum with the goal of effective fluorescence suppression. Combining high repetition rate, picosecond laser pulses and high temporal resolution detection systems with MEMs devices we developed a time gated Raman instrument that is capable of effective fluorescence suppression and producing time-gated Raman maps thanks to the improved signal achievable through compressive detection. Time gated Raman spectroscopy was then investigated for pigmented samples of relevance to cultural heritage and to biology. The instrument was able to recover Raman spectral information of highly fluorescent samples where a typical CCD based Raman instrument with CW laser typically fails. Multilayer samples were measured, and 3D mapping performed. By utilizing multiplexing, depth analysis was measured and calculated via photon time of flight. The design of the instrument was optimized to overcome some of the issues that plague current time gated Raman techniques (portability, low fill factors, temporal resolution). The system uses a single element single photon avalanche diode as the detector to provide the best possible temporal resolution and a digital micromirror device (DMD) as the wavelength selective component to provide a high fill factor for maximum throughput. The DMD allows multiple spectral features to be directed to the detector at any one time (multiplexed compressive detection). The increase in signal from multiplexing allows time gated Raman maps to be performed on a time scale comparable to conventional Raman instruments (seconds per pixel). This study demonstrates the feasibility of time gated Raman mapping for a range of applications.